Assessing the validity of the Structure, Conduct and Performance paradigm as theoretical framework for the application of competition policy in the long-term insurance sector of South Africa - Blaauw, Petrus Arnoldus (Stellenbosch : Stellenbosch University, 2012)
Thesis (MComm.)--University of Stellenbosch, 2001.